Chondral differentiation of induced pluripotent stem cells without progression into the endochondral pathway - Diederichs, Solvig; Klampfleuthner, Felicia; Moradi, Babak; Richter, Wiltrud (Frontiers in cell and developmental biology, 2019)
A major problem with chondrocytes derived in vitro from stem cells is undesired hypertrophic degeneration, to which articular chondrocytes (ACs) are resistant. As progenitors of all adult tissues, induced pluripotent stem cells (iPSCs) are in theory able to form stable articular cartilage. In vitro differentiation of iPSCs into chondrocytes with an AC-phenotype and resistance to hypertrophy has not been demonstrated so far. Here we present a novel protocol that succeeded in deriving chondrocytes from human iPSCs without using pro-hypertrophic bone-morphogenetic-proteins. IPSC-chondrocytes had a high cartilage formation capacity and deposited two-fold more proteoglycans per cell than adult ACs. Importantly, cartilage engineered from iPSC-chondrocytes had similar marginal expression of hypertrophic markers (COL10A1, PTH1R, IBSP, ALPL mRNAs) like cartilage from ACs. Collagen X was barely detectable in iPSC-cartilage and 30-fold lower than in hypertrophic cartilage derived from mesenchymal stromal cells (MSCs). Moreover, alkaline phosphatase activity remained at basal AC-like levels throughout iPSC chondrogenesis, in contrast to a well-known significant upregulation in hypertrophic MSCs. In line, iPSC-cartilage subjected to mineralizing conditions in vitro showed barely any mineralization, while MSC-derived hypertrophic cartilage mineralized strongly. Low expression of IHH like in ACs but rising BMP7 expression like in MSCs suggested that phenotype stability was linked to the hedgehog rather than the BMP pathway. Taken together, unlimited amounts of AC-like chondrocytes with a high proteoglycan production reminiscent of juvenile chondrocytes and resistance to hypertrophy and mineralization can now be produced from human iPSCs in vitro. This opens new strategies for cartilage regeneration, disease modeling and pharmacological studies.